Spatial Distribution of Polycyclic Aromatic Hydrocarbons in Ennore Estuary and Coastal Waters, Chennai, India - Sundararajan, S.; Karthikeyan, R.; Khadanga, Mukunda Kesari (Asian Journal of Chemistry, 2015)
Ennore estuary is one of the major polluted area in Chennai, India due to high pollution load from domestic waste, effluents discharge from petrochemical industries and refineries wastages. Polycyclic aromatic hydrocarbon (PAH) influence due to the petrochemical industries effluent and automobile vehicle transport, movement of ship and fisherman boats. The two rivers named Korattalaiar and Kosasthalaiyar are running along the farming and urban areas carrying all the pollutants, finally entering into the Ennore estuary. Therefore a short term study was conducted to estimate the prevailing concentrations of chrysene (polycyclic aromatic hydrocarbon) contaminants and to know the status of the pollutants. Sea water samples were collected semi-diurnally from Ennore estuary (7 sites) and Chennai Coast (6 sites) for 48 h. The collected samples were extracted by liquid-liquid extraction technique and analyzed by gas chromatography with flame ionization detector. The maximum and minimum mean concentration of chrysene in Ennore estuary during high and low tide was 8.13 and 1.43 mg L-1 and 10.20 and 1.45 mg L-1 respectively. The maximum and minimum mean concentration of chrysene in Chennai coastal waters during high tide and low tide was 1.49 and 0.77 mg L-1 and 2.23 and 1.11 mg L-1 respectively. A relatively high concentration of 10.20 ± 0.10 mg L-1 chrysene was observed in the Buckingham Canal south. This high concentration of chrysene reported in this site due to the discharge of industrial effluents and domestic sewage. The results are showing significant variation spatial as well as temporally.